High-density genetic map and quantitative trait loci map of skin color in hawthorn (Crataegus pinnatifida bge. Var. major N.E.Br.) - Wang, Dongsheng; Cheng, Beibei; Zhang, Jijun (Frontiers in Genetics, 2024)
Fruit skin color is an important trait of the hawthorn tree, which has an important influence on fruit quality. Crataegus pinnatifida Bge. var. major N.E.Br. is one of the most widely cultivated varieties in China and has a long history of medicinal use. In recent years, it has attracted the attention of the world due to its nutritional and medicinal values. Skin color is the focus of breeders and food processors. At present, skin color-related genes have still not been mapped. In this study, 'Shandong Da Mianqiu' (♀, red skin color), 'Da Huang Mianzha' (♂, yellow skin color) and 131 F1 hybrids were used to construct genetic map of hawthorn by RAD-seq, and QTL mapping was performed by combining these features with the hue angle and the observed color. In this study, 13,260 SNP was assigned to 17 linkage groups, with an integrated map covering 2,297.75 cM was constructed. A total of 5 QTLs related to hawthorn skin color were detected on LG1, LG3 and LG15. Whether hue angle or pericarp color acts as phenotype for QTL mapping, the candidate genes include bHLH086, WD repeat regions and Myb-like. bHLH, WD and Myb play an important role in the color regulation of Hawthorn skin color. These results lay a solid foundation for QTL mapping and molecular markerassisted breeding of hawthorn.